Automatic Early Warning System Design with Firefighter Synchronization Based on Internet of Things (IoT) - Elvira Rahayu; Yoyok Heru Prasetyo Isnomo; Mohammad Abdullah Anshori (Politeknik Negeri Malang, 2023)
The fire department or DamKar is one of the important agencies which is highly needed by Indonesian people, especially when a fire occurs. However, DamKar is often judged to be late in arriving at the location because help comes to the fire when the fire has already take a set. One of the reasons why delay happens in DamKar is because the report is received late by the DamKar officer. One of the fire prevention measures is to take the preventive action or early prevention from indications of a fire. Automatic early detection is needed in an emergency and requires speed and accuracy in overcoming the problem. designs an early detection system for fires that directs to DamKar and warehouse owners. This system can detect and provide temperature information in real time. This system works if there is a drastic change in temperature and there is a puff as soon as detected by the sensor The information is in the form of a notification